Applications of Self-Driving Vehicles in an Aging Population - Sara Shu; Benjamin K P Woo (JMIR Formative Research)
AbstractThe proportion of older adult drivers is increasing and represents a growing population that must contemplate reducing driving and eventually stopping driving. The advent of self-driving vehicles opens vast possibilities with practical and far-reaching applications for our aging population. Advancing technologies in transportation may help to overcome transportation barriers for less mobile individuals, transcend social and geographical isolation, and improve resource and medical access. Herein, we propose various applications and benefits that self-driving vehicles have in maintaining independence and autonomy specifically for our aging population to preserve aging.